A cross-cultural study of autistic traits in the general population - Abu Bakar, Safira (2022)
This thesis aimed to explore cross-cultural differences in autistic traits in the Malaysian and British general populations. Freeth et al. (2013) found that Malaysian members of the general population tend to score higher on the Autism Spectrum Quotient (AQ; Baron-Cohen, Wheelwright, Skinner, et al., 2001) compared to British members of the general population, however, it is unclear whether these findings could reflect genuine cognitive differences or whether these findings are the result of a cultural bias in the questionnaires used. For the current research, I looked at each cognitive behaviour described by the subscales of the AQ in isolation to investigate these findings in detail.